Design and optimization of sensors and antennas for wearable devices - Singh, Vinod Kumar, 1977-; Tiwari, Ratnesh, 1982-; Dubey, Vikas, 1985-; Ali, Zakir (Electronics authority); Singh, Ashutosh Kumar (IGI Global, 2020)
"This book examines the use of antennas and sensors in the field of wearable computing"-- Provided by publisher
Keywords: Wearable technology -- Antennas.; Detectors.; elektronické knihy; electronic books